Constructing a Textual Tradition: Salafī Commentaries on al-ʿAqīda al-ṭaḥāwiyya - Shiliwala, Wasim (Die Welt des Islams, 2018)
Although the Salafī movement prides itself on its doctrinal purity, it has recently embraced the creed of Abū Jaʿfar al-Ṭaḥāwī (d. 321/933), which diverges from Salafī beliefs on a few significant topics such as the nature of faith. This paper accounts for this phenomenon by examining the scholarly production around the text, and by considering the strategies employed by modern commentators to deal with problematic lines. I argue that for the Salafī movement, the issues found in this text are outweighed by the polemical imperative of constructing a Salafī textual tradition.